LEGAL ANALYSIS OF LEGAL PROTECTION FOR CHILD VICTIMS OF THE CRIMINAL ACT OF SEXUAL COMMITTED BY CHILDREN (CASE STUDY OF DECISION OF CASE NUMBER: 2/PID.SUS-ANAK/2023/PN. CLP) - Setyadi, Kukuh; Sudarmaji, Aji (Jurnal Hukum Khaira Ummah, 2024)
According to the Child Protection Act, children in conflict with the law are children who are 12 years old but under 18 years old who are suspected of committing a crime. The criminal justice system for children is different from the criminal justice system in general, considering that children need protection. The purpose of this research is to determine the legal protection for child victims of the crime of sexual intercourse in Decision Number: 2 / Pid.Sus-Anak / 2023 / PN. Clp and the judge's considerations in sentencing children who commit the crime of sexual intercourse with minors in Decision Number: 2 / Pid.Sus-Anak / 2023 / PN Clp. The research approach used in this study is through a normative legal approach using secondary data obtained through literature studies, then data analysis is carried out using qualitative descriptive analysis. Based on the results of this study, Law Number 35 of 2014 has regulated the form of legal protection for children, in the Decision of the Cilacap District Court Number 2/Pid.Sus-Anak/2023/PN Clp, children as victims do not receive the rights they should receive, such as legal assistance, rehabilitation, and restitution. This shows a discrepancy between legal provisions and their implementation in the field. The Panel of Judges in Decision Number 2/Pid.Sus-Anak/2023/PN Clp has imposed a criminal sentence of coaching and job training on Child Perpetrators under the age of 14 in accordance with Article 69 of the SPPA Law, where children who are not yet 14 years old can only be subject to action. The judge's considerations in this decision are based on legal and non-legal considerations.